Case Report: Systemic Small-Vessel Vasculitis in an Adolescent With Active Ulcerative Colitis - Bouhuys, Marleen; Armbrust, Wineke; van Rheenen, Patrick F. (Frontiers in Pediatrics, 2021)
Introduction: Small-vessel vasculitis (SVV) is a rare immunological disease that affects arterioles, capillaries and venules. It causes purpura, but can also manifest in other organs, including the gastrointestinal tract. SVV and inflammatory bowel disease (IBD) co-occur more frequently than would be expected by chance. Case description: A 16-year-old girl, who had been diagnosed with ulcerative colitis (UC) 2 years earlier at a general hospital, developed purpura, progressive abdominal pain with frequent bloody diarrhea and frontotemporal headache and swelling while on azathioprine and mesalamine maintenance therapy. Serology was positive for perinuclear antineutrophil cytoplasmic antibodies (p-ANCA) without antiprotease- or myeloperoixidase antibodies. Endoscopy revealed active left-sided UC and atypical ulcerations in the ascending colon. Biopsies of these ulcerations and of affected skin revealed leukocytoclastic vasculitis. Initially this was interpreted as an extraintestinal manifestation of UC that would subside when remission was induced, consequently infliximab was started. Over the next 3 weeks she developed severe burning pain in her right lower leg that progressed to a foot drop with numbness and the purpura progressed to bullous lesions. The diagnosis was adjusted to ANCA-associated vasculitis with involvement of skin, bowel and peripheral nerves. Infliximab was discontinued and induction treatment with high-dose prednisolone and cyclophosphamide was given until remission of SVV and UC was achieved. Subsequently, infliximab induction and maintenance was re-introduced in combination with methotrexate. Remission has been maintained successfully for over 2 years now. The foot drop only partly resolved and necessitated the use of an orthosis. Conclusion: Pediatric patients with IBD who present with purpuric skin lesions and abdominal pain should be evaluated for systemic involvement of SVV, which includes endoscopic evaluation of the gastrointestinal tract. We discuss a practical approach to the diagnosis, evaluation and management of systemic SVV with a focus on prompt recognition and early aggressive therapy to improve outcome.